Cyclodextrins as promoter or inhibitor for methane hydrate formation?. (15th March 2020) - Tian, Linqing; Wu, Guozhong
Highlights: Gas uptake decrease by up to 61% using CD but increase by 83% using CD-SDS mixture. CD increased hydrate formation rate by up to 68% when used together with SDS. CD decreased induction time by one-order of magnitude when used together with SDS. Dosage of SDS for methane hydrate formation can be reduced by 70% by using CD. CD can be changed from promoter to inhibitor by replacing functional groups. Abstract: Hydrate-based separation technology is promising for natural gas storage while sodium dodecyl sulfate (SDS) is one of the most widely used additives to enhance gas hydrate formation, but large-scale application of SDS would pose environmental risks. Cyclodextrins were used as environmentally friendly alternatives in this study aiming to reduce the dependence on SDS usage. Four kinds of cyclodextrins including αCD, βCD, hydroxypropyl-βCD (HPCD) and methyl-βCD (MCD) were used to test the influence of the cyclodextrin's structure and concentration and its interactions with SDS on the methane hydrate formation. Results demonstrated that all the four kinds of cyclodextrins inhibited the gas uptake and water conversion when they were used alone, but some of them could facilitate hydrate formation. When they were used together with SDS, one of the most obvious findings was that the gas hydrate formation was significantly promoted by αCD and βCD but inhibited by HPCD and MCD. Overall results suggested that it was not feasible to completely replace SDS by using cyclodextrin alone but it was possible to reduce the dosage of SDS by about 70%. It also highlighted that the promotion or inhibition effects on hydrate formation was highly associated with the SDS-cyclodextrin complex structure and depended on whether it could form hydrophilic zones through H-bonds between the channel-type complexes.